2007
DOI: 10.1002/ppap.200700066
|View full text |Cite
|
Sign up to set email alerts
|

Arc‐Free Atmospheric Pressure Cold Plasma Jets: A Review

Abstract: Non‐thermal atmospheric pressure plasma jets/plumes are playing an increasingly important role in various plasma processing applications. This is because of their practical capability to provide plasmas that are not spatially bound or confined by electrodes. This capability is very desirable in many situations such as in biomedical applications. Various types of ‘cold’ plasma jets have, therefore, been developed to better suit specific uses. In this paper a review of the different cold plasma jets developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
315
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(337 citation statements)
references
References 72 publications
1
315
0
7
Order By: Relevance
“…A detailed discussion of various properties of barrier discharges and their important industrial applications can also be found in the book Non-Equilibrium Air Plasmas at Atmospheric Pressure by Becker et al [4]. More recent research activities focus on DBD torches [5], on flow control [6] and on biomedical applications [7]. In this contribution the focus is on the discharge physics, mainly on collective phenomena such as filamentation, pattern formation and selforganization, and on the conditions for obtaining diffuse, laterally homogeneous discharges.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed discussion of various properties of barrier discharges and their important industrial applications can also be found in the book Non-Equilibrium Air Plasmas at Atmospheric Pressure by Becker et al [4]. More recent research activities focus on DBD torches [5], on flow control [6] and on biomedical applications [7]. In this contribution the focus is on the discharge physics, mainly on collective phenomena such as filamentation, pattern formation and selforganization, and on the conditions for obtaining diffuse, laterally homogeneous discharges.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the use of plasma in medicine opens up new vistas of novel therapies and medical technologies-a breakthrough that could well become as important as that which was initiated by antibiotics [8]. Of the many systems proposed for the generation of stable atmospheric-pressure plasma, the dielectric barrier discharge (DBD) jet has become the configuration of choice for many researchers [1,2]. A typical plasma jet consists of a capillary formed from a dielectric material through which a noble gas flows.…”
Section: Introductionmentioning
confidence: 99%
“…Low-temperature atmospheric-pressure plasma jets provide a unique opportunity to generate a non-equilibrium gas discharge that is rich in reactive chemical species yet is unbound by any electrode structure [1,2]. In addition to many industrial applications [3][4][5], such devices are finding increasing applications in the field of medicine; promising examples include prion inactivation [6], chronic wound treatment and cancer therapy [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Physically, the breakdown mechanism of APPJs depends strongly on the electron multiplication, which controls the transition from Townsend breakdown to streamer breakdown. 16,17 Since the Townsend ionization coefficient and the mobility of charged species in the electric field depend on the gas properties, the gas type determines the electron multiplication and the breakdown mechanism as well as the discharge mode. In addition, different working gases produce different plasma species resulting in different interactions with the targets.…”
Section: Introductionmentioning
confidence: 99%